2020
DOI: 10.1155/2020/6501272
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anion Gap Predicts All-Cause Mortality in Critically Ill Patients with Acute Kidney Injury: Analysis of the MIMIC-III Database

Abstract: Background. No epidemiological study has investigated the effect of anion gap (AG) on the prognosis of critically ill patients with acute kidney injury (AKI). Therefore, we aimed to determine the association between serum AG and all-cause mortality in these patients. Methods. From MIMIC III, we extracted demographics, vital signs, laboratory tests, comorbidities, and scoring systems from the first 24 h after patient ICU admission. A generalized additive model was used to identify a nonlinear association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…Moreover, critically ill patients are always exposed to hypoxia and anaerobic tissue, which results in the rapid accumulation of pyruvate, and pyruvate may be converted into lactate in some circumstances [ 27 ]. However, patients with AKI always suffer from lactate dehydrogenase dysfunction, and they are not able to clear endogenous acid production, which causes high levels of LDH [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, critically ill patients are always exposed to hypoxia and anaerobic tissue, which results in the rapid accumulation of pyruvate, and pyruvate may be converted into lactate in some circumstances [ 27 ]. However, patients with AKI always suffer from lactate dehydrogenase dysfunction, and they are not able to clear endogenous acid production, which causes high levels of LDH [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim and his team 20 reported that corrected AG in children at ICU admission was associated with mortality, with odds ratio (95% CI) 1.110 (1.06–1.17). Cheng et al, 17 and Tang et al, 21 confirmed a U-shaped relationship between serum AG levels and all-cause mortality in critically ill patients with acute kidney injury and patients with congestive heart failure, respectively. Our findings are consistent with previous studies.…”
Section: Discussionmentioning
confidence: 90%
“…The serum AG has been reported to be associated with death and complications in a variety of diseases. Cheng et al, 17 found that high serum AG values in patients with acute kidney injury had higher all-cause mortality at 30 days, 90 days, and 365 days, HR (95% CI) were: 1.54 (1.33–1.75), 1.55, (1.38–1.73), and 1.46 (1.31–1.60) respectively. Abramowitz et al, 18 found that the serum AG value was associated with mortality, the Relative Hazard (95% CI) was 1.20 (1.03–1.41), and higher levels of serum AG were present in patients with impaired renal function.…”
Section: Discussionmentioning
confidence: 98%
“…Code 577.0 of the ICD-9 speci cation was used to identify 961 patients who were admitted to an ICU with AP for the rst time. [15] We excluded patients with no major laboratory test results or ICU admission severity score within the rst 24 hours, and also patients younger than 18 years. Finally, 850 people who met the inclusion criteria were selected.…”
Section: Patients and Inclusion Criteriamentioning
confidence: 99%